Cinnamaldehyde triggers cell wall remodeling and enhances macrophage-mediated phagocytic clearance of Candida albicans - Shi, Zhaoling; Lin, Jiajia; Li, Wenqian; Chen, Feng; Zhang, Wenna; Yang, Yue; Ma, Kelong (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionCinnamomum cassia, a traditional Chinese medicinal herb, possesses cinnamaldehyde (CIN) with well-documented antifungal and immunomodulatory properties. Although CIN inhibits Candida albicans (C. albicans) growth, its role in macrophage-mediated clearance remains poorly understood.MethodsHere, we evaluated CIN's antifungal activity using MIC determination, spot assays, and time-growth curves. Cell wall disruption (β-glucan and chitin exposure) was assessed by transmission electron microscopy (TEM), confocal laser scanning microscopy (CLSM), and flow cytometry.ResultsTranscriptomic and functional enrichment analyses revealed that CIN compromises cell wall integrity by altering 123 differentially expressed genes (DEGs), particularly those governing hyphal development, cell wall biosynthesis, and biofilm formation. Specifically, CIN downregulated genes associated with β-glucan exposure, mannosylation, and chitin synthesis, and upregulated components of the Cek1/MAPK pathway. CIN-enhanced macrophage phagocytosis significantly increased fungal clearance and reduced fungal escape, as shown by flow cytometry, propidium iodide staining, and lactate dehydrogenase release assays. CIN-pretreated fungi activated the Dectin-1/Syk/CARD9/NF-κB cascade, leading to elevated pro-inflammatory cytokine secretion.DiscussionMechanistically, CIN induces β-1,3-glucan exposure on C. albicans, thereby promoting Dectin-1-mediated phagocytosis and clearance. These findings provide an experimental basis for developing CIN as a novel antifungal therapeutic.